Distribution and Structural Properties of Soils in the Boz Tuproq Region - Parpiyev G’. T.,; Sagdullayev Odiljon Qodirjon o'g'li, (American Journal of Biology and Natural Sciences, 2024)
This article briefly describes the various types of soils in the chernozem region of the Republic of Uzbekistan's land fund, their distribution by genetic groups, their percentage and hectare indicators in relation to the total land area of the republic, and the structural state of these soils (micro- and macro-aggregation) using examples of certain soil types from this region.